Isolation Screening and Characterization of Bio surfactant Produced by Bacillus sp from Automobile Oil Contaminated Soil - Nalini, S (International Journal of Pharmaceutical & Biological Archive, 2013)
Isolation Screening and Characterization of Bio surfactant Produced by Bacillus sp from Automobile Oil Contaminated Soil